Lifestyle and Factors Associated with the Elderly People Referred to the Pension Fund - Neda Barzegar; Maryam Niknami; Leila Mirhadian; Ehsan Kazem Nejad Leili; Sedigheh Pakseresht; M M.Meghachandra Singh (Guilan University of Medical Sciences, 2017)
Abstract Introduction: The world's elderly population is increasing; along with this growth, their health problems gain importance. Meanwhile, healthy lifestyle is a valuable resource for reducing the incidence of health problems and their consequences. It can enhance recovery, deal with life stressors and improve the quality of life. Objective: The present study aimed to assess the lifestyle of elderly people and factors related to it in individuals who were referred to the pension fund in Rasht city. Materials and Methods: This was a cross-sectional study in which 384 members of the pension fund in Rasht city participated. The data collection tools included the demographic questionnaire, the lifestyle questionnaire, including 5 domains of lifestyle and the medical outcomes study-social support survey (MOS–SSS). Data was collected through interviews and then analyzed using the descriptive and inferential statistics, ANOVA, t-test, Spearman s correlation coefficient and regression model. Results: As many as 65.6% of the sample was men and 34.4% women in the age group of 60–65 years. The mean score of lifestyle was 123.82. The results indicated a statistically significant relationship between the lifestyle of elderly people and the absence of chronic illnesses (p=0.022), education level (p=0.006) and housing status (p=0.022). Regression analysis showed that housing, income and social support conditions are factors associated with lifestyle (R² = 0.15, p=0.0001). Conclusion: It was found that the level of education and social support is among the effective factors influencing lifestyle of elderly people. As the lifestyle of most individuals was at a moderate level, it is necessary to conduct training programs of healthy lifestyle for the elderly seriously.